Dietary high level of vitamin premix can eliminate oxidized fish oil–induced oxidative damage and loss of reducing capacity in juvenile largemouth bass (Micropterus salmoides). (30th October 2013) - Yuan, Y.; Chen, Y.J.; Liu, Y.J.; Yang, H.J.; Liang, G.Y.; Tian, L.X.
Abstract Utilizing a 2 × 2 factorial design, four experimental diets (diet LVFF, low‐vitamin premix + fresh fish oil; diet LVOF, low‐vitamin premix + oxidized oil; diet HVFF, high‐vitamin premix + fresh oil; diet HVOF, high‐vitamin premix + oxidized oil) were formulated to investigate the protective role of high level of vitamin premix against the deleterious effects of highly oxidized fish oil (peroxide value, POV: 450 meq kg−1) consumption in juvenile largemouth bass. After a 10‐week feeding trial, survival rates of all treatments were 100%. Neither vitamin premix level nor oil type affected feed intake, growth performance or feed utilization, although treatment HVFF obtained the highest weight gain and specific growth rate, and the lowest feed conversion ratio. Hepatosomatic and viscerosomatic index increased while intraperitoneal fat ratio decreased with rancid oil reception, and they did not benefit from increasing vitamin premix supply. However, dietary high level of vitamin premix ameliorated the decreased whole‐blood haemoglobin content and increased plasma low‐ and high‐density lipoprotein cholesterol levels induced by oxidized oil reception. Whole‐body and liver composition were sensitive to dietary oil oxidation, and vitamin premix addition eliminated the decreased whole‐body lipid content challenged by rancid oil consumption. Hepatic superoxide dismutase activity was stimulated by dietary oil oxidation and increment of vitamin premix abrogated this effect. Dietary oxidized oil inclusion resulted in increased malondialdehyde contents and decreased vitamin E concentrations both in the liver and muscle, and vitamin premix supplementation ameliorated these effects. In conclusion, the results in this study suggested that the well‐ingested oxidized oil could induce severe oxidative damage and loss of reducing capacity in largemouth bass, and dietary high level of vitamin premix could alleviate these effects. This practice is recommended in intensive aquaculture practice in tropical or subtropical regions where oils are susceptible to lipid peroxidation under unsatisfactory storage.